Flipping Expectations: Are Active Learning Strategies Sufficient or Necessary To Teach Principles of Antimicrobial Stewardship in Medical School?. (4th October 2017) - Patel, Roma; Relan, Anju; Vijayan, Tara
Abstract: Background: Teaching principles of antimicrobial stewardship (AS) in medical training is an integral part of developing skills in systems based practices and health policy. While most medical schools have introduced AS concepts in the preclinical years, data on the effectiveness of such curricula are limited. We developed an AS module within the second-year preclinical microbiology course using a "flipped classroom" approach, providing instructional content as webcasts while dedicating lecture time to engaging in case-based content. The purpose of our investigation was to compare the effects of a formal AS curriculum with learning which occurs in a situated, clinical context during core clerkships on performance outcomes. Methods: We administered a knowledge and application-based assessment to second year students who had completed the flipped classroom AS module in their preclinical microbiology course, as well as to third year students who completed their core medicine clerkship but had not had any formal teaching in AS. Mean scores from the total assessment (7 points), knowledge-based questions (4 points) and application-based questions (3 points) were compared using an independent samples t-test. Results: 171 second and 55 third-year medical students completed the assessment. Overall mean scores were significantly higher for MSIIIs (5.47, SD 1.10) compared with MSIIs (4.79, SD 1.40) ( P < 0.01). This difference in scores was due to superior performance on the application-based questions by MSIIIs (2.51, SD 0.63) compared with MSIIs (1.77, SD 1.03) ( P < 0.01). There was no difference on knowledge-based items between MSIIIs (2.96 SD 0.74) and MSIIs (3.02, SD 0.80) ( P = 0.62). Overall scores for MSIIIs completing their medicine clerkship later in the year vs. earlier trended higher (5.69 vs. 5.32, P = 0.60). Conclusion: MSIIIs demonstrated equal knowledge and superior application of AS principles despite not having had a formal curriculum in the subject. Active learning strategies, such as the flipped classroom, may not be able to substitute for experiential learning when it comes to teaching systems based practices such as AS. An iterative approach to teaching AS, starting in the preclinical years, may be more meaningful and warrants further evaluation. Disclosures: All authors: No reported disclosures.